2008
DOI: 10.1002/pd.2018
|View full text |Cite
|
Sign up to set email alerts
|

The best approach for early prediction of fetal gender by using free fetal DNA from maternal plasma

Abstract: DYS14 assay is the best approach for early fetal gender assessment because it is more sensitive, accurate, and efficient than the SRY assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 25 publications
5
51
0
Order By: Relevance
“…The diagnostic sensitivity of the sex detection test is similar to that demonstrated by plasma DNAbased tests (25)(26)(27). However, the chances of urinary DNA contamination are higher than those for plasma DNA, and therefore effective precautions must be used.…”
Section: Discussionmentioning
confidence: 73%
“…The diagnostic sensitivity of the sex detection test is similar to that demonstrated by plasma DNAbased tests (25)(26)(27). However, the chances of urinary DNA contamination are higher than those for plasma DNA, and therefore effective precautions must be used.…”
Section: Discussionmentioning
confidence: 73%
“…Another disadvantage of DYS14 is that it is detected at higher sensitivity than the target gene. 26 For future studies, RASSF1A, a tumour suppressor gene, may be considered as a potentially useful generic marker for circulating fetal DNA. 27 RASSF1A may represent a universal marker because it is differentially methylated in the placenta compared with the genomic DNA of adults.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the higher sensitivity of DYS14, testing for only DYS14 has been suggested. 32,33 However, the inclusion of two multicopy Y-chromosome-specific assays increases the sensitivity and specificity of the test as a whole.…”
Section: Genetics In Medicine | Volume 14 | Number 1 | January 2012mentioning
confidence: 99%
“…30,31 Second, regarding false-positive results, it has been observed that a multicopy sequence, such as DYS14, is more sensitive, accurate, and efficient than the single-copy SRY in the assessment of cffDNA, which is particularly important early in the first trimester of pregnancy when the copy numbers of fetal DNA are low. 32 The drawback of the DYS14 sequence is that it has considerable homology to sequences other than the Y chromosome that could falsely classify female fetuses as male. 33 In comparison with previous studies, 34 we have obtained a high frequency of amplification signals with DYS14 PCR in female fetuses (35% vs. 63.9%).…”
Section: Genetics In Medicine | Volume 14 | Number 1 | January 2012mentioning
confidence: 99%